An investigation into the effects of magnetic fields on biological cell processes - Crotty, Darragh (Trinity College (Dublin, Ireland). School of Physics, 2011)
The application of external magnetic fields to biological cells has received the attention of many researchers in recent decades and there have been countless reports of effects on a myriad of cellular processes. Despite this, there is in general a lack of consensus on the biophysical mechanisms responsible and independent replication of many effects has been unsuccessful. This field of research, often known as bioelectromagnetics, has many potential implications for human health, both in terms of therapeutic applications and concerns about adverse health effects due to fields associated power lines, electrical appliances and mobile telecom and Wi-Fi networks. Magnetic effects on cell processes could also shed new light on the fundamental biophysical/biochemical mechanisms involved. This thesis describes our investigation of a number of static and time-varying magnetic field effects at the cell (osteoblasts and neurons), organelle (mitochondria) and enzyme (creatine kinase) level.
Keywords: Physics, Ph.D.; Ph.D. Trinity College Dublin.